Barks as a Source of Oxalic Acid - I - Bhatia, Kuldip; Lal, Jia; Ayyar, K. S. (Indian Forester, 1985)
Bark samples collected from the trunk portion of mature trees belonging to 31 species were examined for the yield in which oxalic acid could be isolated from them. The bark of Tectona grandis of more than 40 years of age gave oxalic acid in 8.3% to 15.55%) yield. While the bark of Toon ciliata collected from trees growing in the campus of Forest Research Institute was found to contain rich deposits of oxalates (yield of oxalic acid 10.86% to 18.98%), samples of the bark drawn from trees growing in other parts of India gave oxlic acid only in moderate yields of 5.15% to 10.87%. Barks of other species either did not give any oxalic acid or gave it in meagre quantities.